English essentials : - Langan, John (McGraw-Hill Companies,Incorporated, 2009)
John Langan's English Essentials offers guidance through the grammar, punctuation, and usage skills needed for success in college and beyond. In short, English Essentials is an efficient, accessible, and helpful guide to mastering practical English skills.